The effect on new knowledge and reviewed knowledge caused by the positioning task in closed concept maps - Pedro Gabriel Fonteles Furtado; Tsukasa Hirashima; Yusuke Hayashi (The Asia-Pacific Society for Computers in Education (APSCE), 2019)
Abstract The advancement of technology has made it possible for automated feedback to be added to learning activities such as the construction of concept maps. The addition of feedback allows learners to acquire new knowledge instead of only focusing on reviewed knowledge. The cognitive processes for acquiring new knowledge and reviewing knowledge are different, so the benefits of concept maps in past research may not apply to the acquisition of new knowledge. However, how concept map construction varies across these two aspects has not been investigated. This research starts this investigation by researching how the positioning task affects new knowledge and reviewed knowledge. The position task is the act of deciding and managing the position of the elements of the concept map. In this paper, we study the differences in new knowledge and reviewed knowledge across two closed concept map interfaces by comparing test answers. One interface, Kit-build, includes the positioning task. The other interface, Airmap, does not include it. Results suggest that the interfaces only differ in retained reviewed knowledge, having similar performance in immediate new knowledge, immediate reviewed knowledge, and retained new knowledge. Results have potential implications for the general presence of the positioning task in learning interfaces.